Investigation of interactions of different anionic polysaccharides with a cationic surfactant and characterization of nanocapsules derived therefrom - MARIA LEAH, RUBIO (Archīum Ateneo, 2015)
The interaction between polyelectrolytes and oppositely charged surfactants has been known since long but they continue to be the subject of extensive fundamental and applied investigations due to their vast number of applications. In particular, the comb